The role of target costing within new product development - Afonso, Paulo (2007)
This article follows recent research in NPD and target costing to test the relationship between the use of NPD firm practice and the product’s development time and cost. Data was obtained from Portuguese manufacturing firms through a survey. In this study it was found that target costing and reduction of time-to-market together, provide considerable advantages to users of these practices. Such companies can achieve reductions in NPD cycle time and cost without compromising quality and functionality. This paper offers a contribution to current literature by adding empirical evidence on the role of TC within NPD.